2013
DOI: 10.1071/wf12079
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of nutrient losses with eroded sediments by post-fire soil stabilisation techniques

Abstract: Abstract.After an experimental fire in steep shrubland in a temperate-humid region (north-west Spain), the effects of two post-fire stabilisation treatments (grass seeding and straw mulching) on the chemical properties of eroded sediments, and the amount of nutrients lost with them, were evaluated relative to control burnt soil, over a period of 13 months. Total C and N concentrations, and 8 13 C, indicated that sediments were mainly contributed by charred plant and litter material. The highest concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
27
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 43 publications
(98 reference statements)
10
27
3
Order By: Relevance
“…All these authors pointed out that such a post-fire increase was a result of the contribution of ash from burned vegetation and the physiochemical breakdown of Mn complexed with organic matter. This is also likely in our case, because Gómez-Rey et al (2013) found that sediments of the present study were mainly constituted by charred plant and litter material. Although Pivello et al (2010) found a negative correlation between pH and Mn in burned soils, we found a positive correlation (r ¼ 0.633; P , 0.001) between pH KCl and extractable Mn.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…All these authors pointed out that such a post-fire increase was a result of the contribution of ash from burned vegetation and the physiochemical breakdown of Mn complexed with organic matter. This is also likely in our case, because Gómez-Rey et al (2013) found that sediments of the present study were mainly constituted by charred plant and litter material. Although Pivello et al (2010) found a negative correlation between pH and Mn in burned soils, we found a positive correlation (r ¼ 0.633; P , 0.001) between pH KCl and extractable Mn.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, soil-available Mo in these plots was below the detection limit (Gómez-Rey et al 2013), highlighting the importance of the losses of Mo-enriched sediments. Molybdenum is essential for atmospheric N 2 fixation by legumes (Rosolem and Caires 1998), which play an important role in the recovery of N cycling in burnt ecosystems (Hendricks and Boring 1999).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations